Language Transfer in English Pronunciation of Sundanese Speakers at Braga Street, Bandung - Nabilah, Nanda Aidila Fitri; Listiani, Toneng; Firdaus, Dadan (Institut Agama Islam Negeri Palopo, 2025)
This study aims to analyze the phenomenon of language transfer, both positive and negative, on English pronunciation of native Sundanese speakers in Braga Street, Bandung. Employing a descriptive qualitative approach, data were collected through interviews and controlled speech tasks involving 17 participants. The analysis focused on identifying the types, causes, and impacts of language transfer on pronunciation. The findings reveal three forms of negative transfer: substitution, omission, and addition of sounds. Meanwhile, positive transfer is categorized based on similarities in consonants, vowels, and loanwords. Negative transfer patterns generally arise due to phonological differences between Sundanese as the first language (L1) and English as the second language (L2). On the other hand, positive transfer was found to support more accurate pronunciation. These findings offer valuable insights for developing English teaching strategies that strategically address phonological similarities and differences between L1 and L2. Furthermore, this study highlights the importance for tourism practitioners to prioritize effective English communication in order to enhance cross-cultural interactions with international visitors.